INDOCTRINATED IDEOLOGY AND NARRATIVES IN YOUTH FICTION: EMOTIONAL ENGAGEMENT IN HONOR AND SANTA CLAUS IN BAGHDAD BY ELSA MARSTON - Devansh; Singh, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bravely being communicated as innocent literature, Children literature holds power to amuse young minds and efficiently propagate polluted narratives. Investigating literature directed and intended towards children needs, should be handled more carefully as these are the fertile landscapes for propagating and manufacturing ideology and feeding the binaries created by Eurocentric narratives. Elsa Marston’s attempt to write sympathetically about the lives of Arab children but the attempt is covertly an expression of the lens created by the Occident for Orient. Employment of affective narrative that builds on the support of emotions and sympathy are questioning ideological manners which are conditioning young and innocent minds to support and reinforce cultural hierarchies. The deliberate narratives weaved by Marston in Santa Claus in Baghdad and Honor are strategically employing emotions to seduce children to incline towards the idea of West being the saviour and safe heaven. Through incorporation of internal conflict of emotions, pride, culture, individuality and hope into the narrative technique, Marston produces a lasting and corrupted ideological impact through her work. The critical investigation of Elsa’s work would highlight the condition of seemingly innocent text are not didactic or rich text but are powerful ideological texts that are driven or infested with Eurocentric agenda.